2019
DOI: 10.1108/jedt-01-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Neural network models for actual duration of Greek highway projects

Abstract: Purpose This paper aims to examine selected similar Greek highway projects to create artificial neural network-based models to predict their actual construction duration based on data available at the bidding stage. Design/methodology/approach Relevant literature review is presented that highlights similar research approaches. Thirty-seven highway projects, constructed in Greece, with similar type of available data, were examined. Considering each project’s characteristics and the actual construction duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Several studies have attempted to model the relationship between highway projects features and their durations in early stages (Nevett et al, 2021, Titirla and Aretoulis 2019, Son et al, 2019, Okere, 2019, Nani et al, 2017, Pesko et al, 2017. Pesko et al, (2017) concluded that integrating the estimation of duration and cost can compromise the significance of input data, leading to reduction of estimating accuracy compared to that based on separate estimation.…”
Section: Cost and Duration Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have attempted to model the relationship between highway projects features and their durations in early stages (Nevett et al, 2021, Titirla and Aretoulis 2019, Son et al, 2019, Okere, 2019, Nani et al, 2017, Pesko et al, 2017. Pesko et al, (2017) concluded that integrating the estimation of duration and cost can compromise the significance of input data, leading to reduction of estimating accuracy compared to that based on separate estimation.…”
Section: Cost and Duration Estimationmentioning
confidence: 99%
“…As a result, it is generally advised to create more than one predictive model (Elmousalami, 2021). In the current study, Artificial Neural Networks (ANN), Support vector Machines (SVM), and Random Forest (RF) algorithms were selected, as they are commonly used in construction research domain (Elmousalami, 2021, Meharie and Shaik, 2020, Juszczyk, 2020, Titirla and Aretoulis, 2019, Pesko et al, 2017. They were subsequently combined in an ensemble to benefit from their collective strengths and balance their weaknesses.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the reasons for delay for a significant number of the projects were personally witnessed by the author, who has 22 years of professional experience at Egnatia Odos S.A. (EOSA), the client organization responsible for the design, procurement and supervision of the construction of Egnatia Odos Highway and other major and minor road projects in Northern Greece and some of the Greek Islands. Furthermore, EOSA has been a source of data for construction management research in research domains such as actual duration prediction [27], value for money bridge design [39] and construction material consumption and actual cost prediction [40]. Hence, this data collection approach, which is alternative to interviewing or circulating a relevant questionnaire, belongs to a group of methods known as unobtrusive measures [38].…”
Section: Data Collection and Descriptionmentioning
confidence: 99%
“…Waziri (2012a) developed a mathematical model in the form of Bromilow's time-cost model for the prediction of construction time of institutional building projects in North Eastern Nigeria. William (2008) conducted a study to develop mathematical models for the preliminary prediction of highway construction duration, Nani et al (2017) developed a model for forecasting duration for bridge projects, while Titirla and Aretoulis (2019) developed a model to predict the duration of Greek highway projects, while Alemu (2022) developed a model for predicting construction time for public building projects.…”
mentioning
confidence: 99%